THE SERBIAN PENSION SYSTEM IN TRANSITION: A SILENT BREAK WITH BISMARCK - Matković, Gordana; Stanić, Katarina (Economic Annals, 2020)
The pension system in Ser-bia was set up as Bismarckian earnings-related system almost one hundred years ago. At the outset of the transition process at the beginning of 21st Century, the pen-sion system underwent bold reforms. De-spite suggestions from the World Bank to adopt a three-pillar system that would in-volve a break with the Bismarckian heri-tage, reforms concentrated on parametric adjustments that strengthened the link between previous earnings and pension benefits. However, as this paper shows, the Bismarckian earnings-related system has subsequently been silently challenged. On the basis of an analysis of the current and perspective replacement rates for various earning levels and pension variation in-dicators, we show how the contributions/benefit link has been undermined. These policy changes have not been defined or un-derstood as a new strategic course of action, nor have the strategic options been debated and analysed. These silent reforms have seemed to be a “quick and easy” solution to tackle high public expenditures and deficits without understanding their implications, and that breaking up with Bismarck im-plies significant transition costs.